Two pools of IRE1α in cardiac and skeletal muscle cells - Wang, Qian; Groenendyk, Jody; Paskevicius, Tautvydas; Qin, Wenying; Kor, Kaylen C; Liu, Yingjie; Hiess, Florian; Knollmann, Bjorn C; Chen, S R Wayne; Tang, Jingfeng; Chen, Xing-Zhen; Agellon, Luis B; et al. (The FASEB journal, 2019)
The endoplasmic reticulum (ER) plays a central role in cellular stress responses mobilization of ER stress coping responses, such as the unfolded protein response (UPR). The inositol-requiring 1α (IRE1α) is an ER stress sensor and component of the UPR. Muscle cells also have a well-developed and highly subspecialized membrane network of smooth ER called the sarcoplasmic reticulum (SR) surrounding myofibrils and specialized for Ca storage, release, and uptake to control muscle excitation-contraction coupling. Here, we describe 2 distinct pools of IRE1α in cardiac and skeletal muscle cells, one localized at the perinuclear ER and the other at the junctional SR. We discovered that, at the junctional SR, calsequestrin binds to the ER luminal domain of IRE1α, inhibiting its dimerization. This novel interaction of IRE1α with calsequestrin, one of the highly abundant Ca handling proteins at the junctional SR, provides new insights into the regulation of stress coping responses in muscle cells.-Wang, Q., Groenendyk, J., Paskevicius, T., Qin, W., Kor, K. C., Liu, Y., Hiess, F., Knollmann, B. C., Chen, S. R. W., Tang, J., Chen, X.-Z., Agellon, L. B., Michalak, M. Two pools of IRE1α in cardiac and skeletal muscle cells.